KEPUASAN PELAYANAN DI PT PEGADAIAN (PERSERO) UNIT UNSRAT - ASSA, RAINDY; RURU, JOORIE; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: Review of services provided by PT. Pegadaian in the study oo publik administration can not beseparated from the study in the view of New Public Management paradigm. Scope of services and public services(public services) covering aspects of community life as a target service of customers. Quality service isconfronted to give the papacy to society, the satisfaction of society no only to the acceptance of a service for theneeds of society, but also related to what happened and happened to the society when the service was processed.This research was conducted to explain the satisfaction of service ftom PT. Pegadaian Unit Unsrat BranchManado in the study of publik administration disciplines.The research uses qualitative research design with descriptive analysis by focusing on perceived value and userexpectation of service. Data obtained through interviews with head unit information, customer service, staf andcustomers, followed by observation and tracing documents related to the object of research. The data obtainedfrom the field in analyzed through the categorization stage and reduces the data, arrangement in the form ofnarratives, interpretation, conclusing and verivication of data analysis.Meet the urgent of the community. The expectations of service users are met in terms of fonding needs whilestill adbering to company policies. However, it has not been adapted to the development of informationtechnology such as service in the form of drive thru and delivery. Based on exixting conclusions, in order toimprove the problem it is advisable that the need to improve the location of the office, the large parking lot. Thespecial service waiting room fot the disabled and the riderly, teinforce in innovative work culture, high moralvalues and skilled through customer satification tranning to mainten the value of service which is felt by thecommunity and innovated thr form of service by adjusting to the development of information technology stachas service in the form of drive thru and delivery.Keywords : Satisfaction, Service, Customer